THE EFFECTIVENESS OF DICTATION METHOD TOWARD STUDENTS’ ABILITY IN WRITING RECOUNT TEXT OF EIGHTH GRADE AT SMP NEGERI 37 MEDAN - Friska Damayanti Sitorus; Fenty Debora Napitupulu; Sahat Taruli Siahaan (Sean Institute, 2023)
The objective of the study is intended to find out the effect of Dictation Method on students